Psychological Stability from The Perspective of Islamic Law: Analytical Purpose Study - Shanaz Hazal Rasoul; Omar Hassan Saeed; Badrakhan Mustafa Ibrahim (QALAAI ZANIST JOURNAL, 2023)
Psychological stability is a necessary part in building a healthy person and a moderate personality. The goal of all heavenly religions is to achieve happiness in this world and the hereafter. Balance between the interests and the evils, and managing himself, his spirit and his dignity in the costs, duties and prohibitions that God Almighty has set as a test for him in this world. Whenever a person settles down and feels it, and is reassured about the law and the cost of God, he finds the pleasure of commitment and drawing closer to God Almighty, and he controls his whims and motives and directs them to the pleasure of the Lord Almighty. A person can benefit from his intellectual, mental and financial energies. The research is an attempt to demystify the importance of psychological stability in Islamic law in order to preserve religion from heresies, the mind from corruption, the soul from destruction, money from loss, honor and lineage from perversion.